THE INFLUENCE OF STRATEGIC ADVERTISING AND STORE ATMOSPHERE ON CUSTOMER BUYING INTERESTS - Murwanto Sigit (Journal of Management and Business, 2014)
This study aims to determine: (1) the influence of advertising and store atmosphere partially on consumer buying interest at Giant Supermarket, (2) the effect of the influence of advertising and store atmosphere simultaneously on consumer buying interest at Giant Supermarket, and (3) between advertising and store atmosphere, which one that has the most dominant influence on consumer buying interest at Giant Supermarket.This research is a survey using quantitative approach. The population in this study is all visitors at Giant Supermarket. The method of taking the sample is purposive sampling with sample of 100 people. Data were collected by questionnaire that has been tested for validity and reliability. The data analysis technique used is multiple regressions.The results of this study indicate that: (1) There is the influence of advertising on consumer buying interest at Giant Supermarket, evidenced from the tcount value of 4.228 is greater than ttable value of 1.987 or (4.228> 1.987); with a significance value of 0.000 <0.05; and the regression coefficient has positive value of 0.221; (2) There is store atmosphere influence on consumer buying interest at Giant Supermarket, evidenced from tcount of 4,895 larger than ttable value of 1.987 or (4.895> 1.987); with a significance value of 0.000 <0.05, and the regression coefficient has positive value of 0.435; (3) There is the influence of advertising and store atmosphere on consumer buying interest at Giant Supermarket, evidenced from the results obtained by the F-test analysis F_count value of 37.679; when compared with the value of 3.111 F_table at significance level of 5%, then the value F_count> F_table (37.679> 3.111), with a significance value of 0.000 is smaller than 0.05 (0.000 <0.05), and (4) store atmosphere that has the most dominant influence on consumer buying interest at Giant Supermarket, evidenced by regression coefficient of 0.435.